CENTROID-MOMENT TENSOR SOLUTIONS FOR APRIL-JUNE 1986 - Dziewonski, A; Ekstrom, G; Franzen, J; Woodhouse, J (1987)
Centroid-moment tensor solutions are presented for 203 earthquakes that occurred during the second quarter of 1986. The solutions are obtained using corrections for aspherical Earth structure. © 1987.